Corporate social responsibility in urban transport cooperatives in Portoviejo, Manabí province, Ecuador - Tualombo Tituaña, José; Flores Urbáez, Matilde (mktDESCUBRE; Vol 1 No 15 (2020): Fifteenth Edition (January - June), 2020)
The purpose of this research is to analyze the social enterprise responsibility from the perspective of the managers of the urban public transport cooperatives that operate in the Portoviejo canton, Manabí province, Ecuador.It was a field research, its scope was descriptive and exploratory and its design was non-experimental-transversal. A questionnaire was applied to the management of the transport cooperatives at Portoviejo, Ciudad del Valle and Picoazá. The questionnaire content validation of the   was carried out through expert judgment and its reliability through the calculation of the Cronbach alpha coefficient. Among the main results, it stands out that in general the managers of the cooperatives studied consider the social enterprise responsibility to be important, they know about the advantages of being socially responsible and carry out corporate social responsibility actions. It is concluded that transport cooperatives need to incorporate the social enterprise responsibility formally as a competitive strategy to further favor their community, the conservation of the environment and their members.